Imitation (In)Security: Cultivating Mimetic Theory to Critique the Media/Security Nexus. Issue 1 (17th November 2016) - Taylor, Bryan C.
Abstract: Contemporary media culture frequently associates security with imitation. This essay theorizes critique of related textuality within the contemporary "media/security nexus." It advocates for enhanced usage of mimetic theory to critique media representation of security, as that condition is pursued through cultural practices of adaptation, disguise, and simulation. Two competing traditions of mimetic theory are reviewed, along with their appropriations in the fields of media studies and security studies. Four benefits are proposed for mimetic critique of "media/security." The essay concludes by considering the ethical and political stakes of this critique .